Biosynthetic Potential of Bioactive Streptomycetes Isolated From Arid Region of the Thar Desert, Rajasthan (India) - Masand, Meeta; Sivakala, Kunjukrishnan Kamalakshi; Menghani, Ekta; Thinesh, Thangathurai; Anandham, Rangasamy; Sharma, Gaurav; Sivakumar, Natesan; Jebakumar, Solomon R. D.; Jose, Polpass Arul (Frontiers in Microbiology, 2018)
Acquisition of Actinobacteria, especially Streptomyces from previously underexplored habitats and the exploration of their biosynthetic potential have gained much attention in the rejuvenated antibiotics search programs. Herein, we isolated some Streptomyces strains, from an arid region of the Great Indian Thar Desert, which possess an ability to produce novel bioactive compounds. Twenty-one morphologically distinctive strains differing in their aerial and substrate mycelium were isolated by employing a stamping method. Among them, 11 strains were identified by a two-level antimicrobial screening method, exerting antimicrobial effects against a panel of indicator strains including methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus species. Based on their potent antimicrobial activity, four isolates were further explored by 16S rRNA gene-based identification, genetic screening, and metabolomic analysis; and it was found that these strains belong to the genus Streptomyces. The selected strains were found to have polyketide synthase and nonribosomal peptide synthetase systems. In addition, extracellular metabolomic screening revealed that the isolates produced analogs of doxorubicinol, pyrromycin, erythromycin, and 6−13 other putative novel metabolites. These results demonstrate the significance of Streptomyces inhabiting the arid region of Thar Desert, suggesting that similar arid environments can be considered as the reservoirs of novel Streptomyces strains that could have biotechnological significance.